Spatial distribution of tidal flooding in the coastal areas of Demak Regency, Central Java - Adnan Bayu; Endriani Arhatin Risti; Lumban-Gaol Jonson; Budi Susilo Setyo (BIO Web of Conferences)
The melting of polar ice caps due to climate change has resulted in sea level rise that threatens coastal areas, such as the Demak Regency. The impact of tidal flooding is, exacerbated by land subsidence. This study aimed to map and predict the distribution of tidal flooding in coastal Demak and its impact on land use. The methods used included Differential Interferometry Synthetic Aperture Radar (DInSAR) for Land Subsidence (LS), supervised classification for land use, admiralty for tides, data visualization for elevation, linear regression analysis for SLR, meteorological data analysis for wind and rainfall, and spatial analysis for tidal flood inundation mapping. The results showed an LS rate of 2,74 cm/year, highest tide height of 61,93 cm, average elevation of 1,893 m above sea level, SLR rate of 0,435 cm/year, wind speed of 0,5-5,7 m/s blowing from the northwest, and average daily rainfall of 7,476 mm. The tidal flood inundation area in 2023 reached 8.954,6 hectares and is predicted to reach 11.394,5 hectares in 2031. Tidal flooding affects mangroves (523,6 hectares), ponds (3.857,9 hectares), settlements (1.095,4 hectares), industries (3.453,00 hectares), and rice fields (24,7 hectares).